2011
DOI: 10.1002/ajmg.a.34169
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of variants in and near the IRF6 gene to the risk of nonsyndromic cleft lip with or without cleft palate in a Malay population

Abstract: Several studies have shown evidence for the contribution of interferon regulatory factor 6 (IRF6) variants to the risk of nonsyndromic oral clefts in Asians; however, this has not included the Malay population. The current study attempts to address this research gap using allele and haplotype transmission disequilibrium analyses. The results showed a strong transmission distortion for multiple haplotypes to patients with nonsyndromic cleft lip with or without cleft palate. Haplotypes carrying the 243 bp allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Later, this same group revealed that the association of rs2235371 with the disease is dependent of rs642961, a polymorphism that disrupts the binding site of the transcription factor AP‐2a in the IRF6 promoter, which is in strong linkage disequilibrium with rs2235371 (Rahimov et al, ). The association of IRF6 variants with NOC has been replicated in various populations (Birnbaum et al, a; Huang et al, ; Krasone et al, ; Mijiti, Ling, Guli, & Moming, ; Moreno Uribe et al, ; Park et al, ; Salahshourifar, Sulaiman, Zilfalil, & Halim, ; Tang et al, ; Tomita et al, ) and supported by animal studies (Ingraham et al, ; Iwata et al, ). Nevertheless, this association has not been identified in studies of African cohorts (Butali et al, ; Figueiredo, Ly, & Raimondi, ; Weatherley‐White et al, ).…”
Section: Discussionmentioning
confidence: 87%
“…Later, this same group revealed that the association of rs2235371 with the disease is dependent of rs642961, a polymorphism that disrupts the binding site of the transcription factor AP‐2a in the IRF6 promoter, which is in strong linkage disequilibrium with rs2235371 (Rahimov et al, ). The association of IRF6 variants with NOC has been replicated in various populations (Birnbaum et al, a; Huang et al, ; Krasone et al, ; Mijiti, Ling, Guli, & Moming, ; Moreno Uribe et al, ; Park et al, ; Salahshourifar, Sulaiman, Zilfalil, & Halim, ; Tang et al, ; Tomita et al, ) and supported by animal studies (Ingraham et al, ; Iwata et al, ). Nevertheless, this association has not been identified in studies of African cohorts (Butali et al, ; Figueiredo, Ly, & Raimondi, ; Weatherley‐White et al, ).…”
Section: Discussionmentioning
confidence: 87%
“…The exon 7 of IRF6 gene encodes for major region of the C-terminal IAD region and hence mutations within this region may be expected cause functional impairment. Indeed, a single point mutation that causes conversion of GTC to ATC creating valine to isoleucine substitution at position 274 in IRF6 protein has been found to be significantly associated with cleft in several populations (Mangold et al, 2011;Salahshourifar et al, 2011;Stuppia et al, 2011). The identification of loss of IRF6 expression due to promoter hypermethylation of IRF6 in cutaneous squamous cell carcinomas and function impairing mutations in exon 7 of IRF6 in CL/CP/CLP prompted us to investigate, whether such mutations occurred in well differentiated OSCC lesions.…”
Section: Introductionmentioning
confidence: 99%
“…an association between IRF6 and NSCLP (10-13;[16][17][18][19][20][21][22][23] suggests that this is an important gene and clearly warrants further study. Though this study does not indicate that…”
mentioning
confidence: 99%